“In our culture, if you quarantine someone, you stigmatize them”: Qualitative insights on barriers to observing COVID-19 prevention behaviors in Côte d’Ivoire - Natalie Jean Tibbels; Abdul Dosso; Kouamé Walter Kra; Konan Dorgeles Gbeke; Gervais Coffi; Alex Romeo Ngoran; Jean Louis Niamke; Marjorie Nana; William Benié; Zoé Mistrale Hendrickson; Danielle Amani Naugle (PLOS Global Public Health, 2022)
While vaccines are now authorized for use against the SARS-CoV2 virus, they remain inaccessible for much of the world and widespread hesitancy persists. Ending the COVID-19 pandemic depends on continued prevention behaviors such as mask wearing, distancing, hand hygiene, and limiting large gatherings. Research in low- and middle-income countries has focused on the prevalence of adherence and demographic determinants, but there is a need for a nuanced understanding of why people do or do not practice a given prevention behavior. The Breakthrough ACTION project led by Johns Hopkins Center for Communication Programs conducted a qualitative study in November 2020 in Côte d’Ivoire to explore people’s experience with and perceptions of the COVID-19 pandemic. We conducted 24 focus group discussions and 29 in-depth interviews with members of the general population and health providers. This analysis explores barriers and facilitators to seven recommended prevention behaviors with a particular focus on response efficacy, self-efficacy, and social norms. We found these constructs to be salient for participants who generally felt that the behaviors were useful for preventing COVID-19 but were difficult to practice for a variety of reasons. The perception that COVID-19 prevention behaviors were anti-social emerged as a key theme. Behavior change interventions must reframe the recommended behaviors as pro-social, while making them very easy to practice by removing social and structural barriers such as the expense or inaccessibility of masks and hand sanitizer.